Do oil-in-water (O/W) nano-emulsions have an effect on survival and growth of bacteria?. (November 2017) - Kadri, Hani El; Devanthi, Putu Virgina Partha; Overton, Tim W.; Gkatzionis, Konstantinos
Abstract: Nano-emulsions (typically droplet diameter < 1 μm) are common in foods, and have been extensively reported to present antimicrobial activity, however, the mechanism is not well defined, and some studies reported no effect. A review of the literature was conducted and revealed strongly contradictory reports regarding the antimicrobial effect of nano-emulsions even in reference to similar microbial species and formulations. Following up, this study aimed to investigate the effect of nano-emulsions on four bacterial species ( Staphylococcus epidermidis, Bacillus cereus, Lactobacillus acidophilus and five Escherichia coli strains) possessing different surface charge and hydrophobicity. Model oil-in-water (O/W) emulsions with different size of oil droplets were prepared with sunflower oil stabilised by polysorbate 80 (Tween80) emulsifier (hydrophilic), using high shear mixing followed by ultrasonication. The viability of bacteria was monitored by culture, membrane integrity was assessed with flow cytometric analysis with propidium iodide (PI) staining and fluorescence microscopy monitored the spatial distribution of cells within the O/W emulsions. The stability of the nano-O/W emulsions in the presence of bacteria was assessed by monitoring the droplet size [D (4, 3)] and creaming height. In contrast to other reports the survival and growth of bacteria was not affected by the size of the oil droplets, no damage to the bacterial membrane was evident with flow cytometry and emulsion stability was not affected by the presence of bacteria during 7 days of storage. Furthermore, the antimicrobial activity of caprylic acid (CA) was compared between O/W coarse and nano-emulsions while varying the concentration of the hydrophilic surfactant Tween80. The activity of CA was similar in nano-emulsion and coarse emulsion; however, it was higher than in bulk oil and was reduced with increasing Tween80 concentration, suggesting that its efficacy is dictated by formulation rather than oil droplet size. The results demonstrated no enhanced antimicrobial activity due to nano-sized oil droplets and that conclusions on nano-emulsions should be taken with caution. Graphical abstract: Highlights: Nano droplets in oil-in-water (O/W) emulsions had no direct antimicrobial properties. Contradictory results in literature discussing the antimicrobial activity of nanoemulsions. Increasing Tween80 reduced the antimicrobial activity of caprylic acid in emulsion. Stability of O/W emulsion was not affected by the presence of bacteria. The O/W emulsions were not affected by cell ζ-potential and hydrophobicity.